The responsibility to understand : hermeneutical contours of ethical life - George, Theodore D., 1971- (Contemporary continental ethics., 2020)
Theodore George makes a novel case for a distinctive sense of responsibility at stake in the hermeneutical experiences of understanding and interpretation.